Detection of Procedural Errors with Stainless Steel and NiTi Instruments by Undergraduate Students Using Conventional Radiograph and Cone Beam Computed Tomography - Alves, Régis Augusto Aleixo; Souza, João Batista; Alencar, Ana Helena Gonçalves; Pécora, Jesus Djlama; Estrela, Carlos (Iranian Endodontic Journal, 2013)
Introduction: This study investigated procedural errors made during root canal preparation using stainless steel and nickel-titanium (NiTi) instruments by undergraduate students, using two diagnostic imaging methods. Materials and Methods: Sixty human molars were divided into three groups (n=20; group 1: K-Flexofile, group 2: K3, and group 3: BioRace). The root canals were filled with gutta-percha and AH Plus. Periapical radiographs and cone beam computed tomography (CBCT) images were obtained to detect procedural errors made by undergraduate students during root canal preparation. Two examiners evaluated the presence or absence of fractured instruments, perforations and canal transportations. The agreement between observers was assessed using the kappa coefficient. The Kolmogorov-Smirnov, Fisher exact, ANOVA and Tukey tests were used for statistical analysis. The level of significance was set at 5%. Results: There were no significant differences in detecting procedural errors between two- and three-dimensional diagnostic imaging methods. There were no significant differences in procedural errors between stainless steel and NiTi instruments. Mean preparation time was recorded in minutes, and results were significantly different between the three groups. NiTi instruments had the lowest mean preparation time. Conclusion: Both periapical radiographs and CBCT identified procedural errors, however, three-dimensional images offered more diagnostic resources. The frequency of procedural errors was low for any of the endodontic instruments despite being used by inexperienced operators.